Clopidogrel dose adjustment after outpatient screening for CYP2C19 variant alleles: a pilot study. (May 2014) - Rossi, Joseph S; Cammarata, Michael; Dharmavaram, Jayalalitha; Weck, Karen; Walko, Christine; Gabriel, Don; Kuritzky, Jack; Muldrew, Kenneth; Stouffer, George A
This pilot study examined the feasibility of outpatient screening and clopidogrel dose adjustment for patients with previous percutaneous coronary intervention and at least one CYP2C19 loss-of-function allele. After screening a total of 211 outpatients, 50 patients were enrolled in a crossover study comparing 30 days of standard dose (75 mg) to 30 days of high-dose clopidogrel (150 mg). Platelet function was assessed with the VerifyNow P2Y12 assay. In patients with CYP2C19*2, 150 mg daily of clopidogrel was associated with improved ADP-specific platelet inhibition (217 vs 258 P2Y12 reaction units, p = 0.01). Outpatient screening for CYP2C19 loss-of-function polymorphisms is feasible, and a strategy of clopidogrel dose escalation may improve platelet inhibition in appropriately selected patients.